Macroeconomic coordination and commercial integration in MERCOSUR - Afonso S. Bevilaqua (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1997)
Commercial integration in the Mercosur area has increased substantially in the last few years and it is expected to continue to grow rapidly in the near future. However, given the historical record of policy management in the region, especially in Brazil and Argentina, the main partners of this integration initiative, it is not clear whether macroeconomic policies will provide the required conditions of sustainability for such a rapid trade expansion. This paper discusses the relationship between macroeconomic coordination and commercial integration in the context of Mercosur. After examining the impact of policy instability on trade flows within the region in recent years, it evaluates the prospects for closer coordination of macroeconomic policies in the future.
Keywords: F15; F36; F42; 330